PENGEMBANGAN APLIKASI PENJADWALAN PRAKTIKUM MENGGUNAKAN ALGORITMA GENETIK DI LABORATORIUM KOMPUTER FAKULTAS TEKNOLOGI INFORMASI - COMPUTING INFORMATIKA; Rustiyana; Rosmalina (COMPUTING | Jurnal Informatika, 2022)
ABSTRACT: Scheduling is an information medium used to facilitate the timing of the implementation of activities. As well as the implementation of the practicum at the Faculty of Information Technology, Bale Bandung University which determines the schedule using a scheduling application. However, in this practicum scheduling application, you can still input the same data and of course this can cause the practicum schedule to conflict. So to avoid the similarity of the practicum schedule data, it must be checked again manually. This practicum scheduling application needs to be developed again so that the implementation of the practicum will be helped more easily and practically. The development of this practicum scheduling application uses genetic algorithms to avoid the same data and recommend non- conflicting schedules. In the process of developing the application, practicum scheduling is carried out using the System Development Life Cycle (SDLC) waterfall model method with stages of analysis, design, implementation and testing. In addition to scheduling avoiding conflicts and displaying schedule recommendations using genetic algorithms plus also by using the add, edit and delete features multiple in one action to make it easier for users to process data, especially practical data, because every year they have to input practices or new students.